Complete mitochondrial genome of the fennec fox (Vulpes zerda). (2nd January 2016) - Yang, Xiufeng; Zhao, Chao; Zhang, Honghai; Zhang, Jin; Chen, Lei; Sha, Weilai; Liu, Guangshuai
Abstract: In this study, the complete mitochondrial genome of the fennec fox ( Vulpes zerda ) was sequenced using blood samples obtained from a female individual in Shanghai wildlife Park. Sequence analysis showed that the content of T (26.7%) in total composition was no more than C (27.2%), which is different from most of Canide individuals sequenced previously.